Fungal Infections as an Uprising Threat to Human Health: Chemosensitization of Fungal Pathogens With AFP From Aspergillus giganteus - Dhandapani, Kavitha; Sivarajan, Karthiga; Ravindhiran, Ramya; Sekar, Jothi Nayaki (Frontiers in Cellular and Infection Microbiology, 2022)
Occurrence and intensity of systemic invasive fungal infections have significantly risen in recent decades with large amount of mortality and morbidity rates at global level. Treatment therapy lies on the current antifungal interventions and are often limited due to the emergence of resistance to antifungal agents. Chemosensitization of fungal strains to the conventional antimycotic drugs are of growing concern. Current antifungal drugs often have been reported with poor activity and side effects to the host and have a few number of targets to manifest their efficacy on the pathogens. Indiscriminately, the aforementioned issues have been easily resolved by the development of new intervention strategies. One such approach is to employ combinational therapy that has exhibited a great level of inhibitions than that of a single compound. Chemosensitization of pathogenic mycoses to commercial antifungal drugs could be drastically enhanced by co-application of chemosensitizers along with the conventional drugs. Chemosensitizers could address the resistance mechanisms evolved in the pathogenic fungi and targeting the system to make the organism susceptible to commercially and clinically proven antifungal drugs. However, this strategy has not been overreached to the greater level, but it needs much attention to fight against not only with the pathogen but combat the resistance mechanisms of pathogens to drugs. Natural compounds including plant compounds and microbial proteins act as potential chemosensitizers to break the resistance in mycoses. Aspergillus giganteus, a filamentous fungus, is known to produce a cysteine rich extracellular protein called as antifungal protein (AFP). AFP has shown enhanced efficacy against several filamentous and non-filamentous fungal pathogens. On the basis of the reported studies on its targeted potential against pathogenic mycoses, AFP would be fabricated as a good chemosensitizer to augment the fungicidal efficacy of commercial antimycotic drugs. This paper reviews on breakthrough in the discovery of antifungal drugs along with the resistance patterns of mycoses to commercial drugs followed by the current intervention strategies applied to augment the fungicidal potential of drugs.